2010
DOI: 10.1108/13639511011020647
|View full text |Cite
|
Sign up to set email alerts
|

Electronic control devices and use of force outcomesIncidence and severity of use of force, and frequency of injuries to arrestees and police officers

Abstract: PurposeThis paper seeks to address a deficit in the criminal justice literature by examining patterns of electronic control device (ECD) use and effectiveness as reflected in 1,188 official police use‐of‐force report records collected over a three‐year period (2005‐2007) by the Washington State Patrol (WSP).Design/methodology/approachChi‐square, t‐test, ANOVA and logistic regression analysis were employed to analyze the data with respect to patterns of use and outcomes for officers and arrestees.FindingsThe fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(52 citation statements)
references
References 61 publications
(89 reference statements)
0
50
0
Order By: Relevance
“…Varying forms of these measures have been included in previous examinations regarding citizen injuries (e.g., Lin & Jones, 2010;MacDonald et al, 2009;PERF, 2009;Smith et al, 2007) as well as broader use of force research (Terrill and Mastrofski, 2002). 16 Three primary officer-based characteristics also are included that have been part of previous empirical studies of police behavior in general (Riksheim & Chermak, 1993), the use of force (Paoline & Terrill, 2007;Worden, 1996), and CEDs and citizen injuries (Lin & Jones, 2010;Smith et al, 2007). More specifically, we accounted for officer sex, race, and experience in the event that these factors are related to individual-level differences in the application of CEDs and potentially resulting injuries to citizens.…”
Section: Control Measuresmentioning
confidence: 99%
See 2 more Smart Citations
“…Varying forms of these measures have been included in previous examinations regarding citizen injuries (e.g., Lin & Jones, 2010;MacDonald et al, 2009;PERF, 2009;Smith et al, 2007) as well as broader use of force research (Terrill and Mastrofski, 2002). 16 Three primary officer-based characteristics also are included that have been part of previous empirical studies of police behavior in general (Riksheim & Chermak, 1993), the use of force (Paoline & Terrill, 2007;Worden, 1996), and CEDs and citizen injuries (Lin & Jones, 2010;Smith et al, 2007). More specifically, we accounted for officer sex, race, and experience in the event that these factors are related to individual-level differences in the application of CEDs and potentially resulting injuries to citizens.…”
Section: Control Measuresmentioning
confidence: 99%
“…4 The findings indicated that chemical spray had the greatest impact on reducing the odds of a suspect injury, followed by CEDs. Lin and Jones (2010), utilizing 708 use-of-force incidents from the Washington State Patrol (WSP), also examined the probability of citizen injury as a result of electronic control devices (ECDs) (a synonym for CEDs). The researchers dichotomized their force variable to include instances where ECDs were used versus all other force applications that did not involve an electronic weapon, and incorporated six control variables.…”
Section: Prior Ced and Citizen Injury Examinationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to this larger body of literature, however, recent findings regarding the use of one type of weapon-conducted energy weapons (CEWs) 1 -have generated relatively consistent findings. Most recent studies of the use of CEWs by police have shown that they substantially reduce the number and severity of injuries to citizens compared to other types of force and have similar effects on injuries to officers or are benign (Lin & Jones, 2010;Smith, Kaminski, Rojek, Alpert, & Mathis, 2007;Taylor & Woods, 2010). Notably, the only two studies to date employing quasi-experimental designs bolster confidence in these results Taylor & Woods, 2010).…”
Section: Introductionmentioning
confidence: 83%
“…Using more sophisticated research designs and statistical methods, several independent studies have since been conducted, with the majority reporting that the use of CEWs significantly reduced injuries to suspects and/or officers as well as the severity of injuries to suspects (Lin & Jones, 2010;MacDonald et al, 2009;Paoline, Terrill, & Ingram, 2012;Smith et al, 2007;Taylor & Woods, 2010). Further these studies reported that the risk of moderate to severe harm from the use of CEWs was quite low.…”
Section: Cews and Nonfatal Officer And Suspect Injuriesmentioning
confidence: 93%